A New Solution for Projective Reconstruction Based on Coupled Line Cameras. Issue 5 (1st October 2013) - Lee, Joo‐Haeng
Abstract : We provide a new solution for the projective reconstruction problem based on coupled line cameras (CLCs) and their geometric properties. The proposed solution is composed of a series of optimized steps, and each step is more efficient than those of the initial solution proposed in [1]. We also give a new determinant condition for rectangle determination, which leads to less ambiguity in implementation. The key steps of the proposed solution can be represented with more compact analytic equations due to the intuitive geometric interpretations of the projective reconstruction problem based on CLCs: the center of projection corresponds to the intersection point of the two solution circles of each line camera involved.